INFLUENCE OF DIVIDEND POLICY AND PROFITABILITY ON STOCK PRICE IN CONSUMER NON-CYCLICALS COMPANIES IN INDONESIA FROM 2018 TO 2022 - Ignatius, Bayiuaji; Lestari, Henny Setyo (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to analyze the influence of dividend policies and profitability on stock prices in non-cyclical consumer companies during 2018-2022. A panel data analysis method is employed to link variables such as dividend capacity, dividend payout, dividend per share, return on assets, return on equity, capital structure, and firm size to changes in stock prices. The research findings reveal that dividend capacity and firm size have a significant negative impact on stock prices, while dividend per share, return on assets, and capital structure have a significant positive impact. Dividend payout and return on equity do not have a significant influence on stock prices. These findings offer insights into the factors affecting stock prices in this industry, provide guidance for companies in designing dividend policies and profitability strategies, and offer valuable information to investors for decision-making.